Effect of arbuscular mycorrhizae and phosphorus on seedling growth of Casuarina equisetifolia - and R. NARAYANAN, E. RAJESWARI, T.K.S. LATHA, K. VANANGAMUDI, K. ARULMOZHI SELVAN (Indian Phytopathology, 2002)
Seedling growth and vigour of casuarina [Casuarina equisetifolia (Frost.)] raised in polybags were evaluated after inoculating nursery soil mixture with 3 cultures of Arbuscular Mycorrhizae (AM) along with 3 levels of fertilizer phosphorus (0,300 and 500 mg/polybag). AM inoculated seedlings grew faster and healthier than uninoculated seedlings, Among AM cultures, Glomus fasiculatum was found to be efficient. When combined with P at 300 mg/polybag its efficiency was greater and produced robust seedlings with longer root and shoot as well as higher drymatter and P uptake. However, when P was applied at 500 mglpolybag in combination with cultures, AM colonisation appreciably decreased and no improvement in growth of seedlings was observed.